Incidentally detected PET-avid liver adenomatosis: MRI and 18F-FDG PET-CT findings - Öz, Ayşegül; Koyuncu Sökmen, Bedriye; İnan, Nagihan and Balcı, Numan Cem and Tokat, Yaman (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Öz A, Koyuncu Sökmen B, İnan N, Balcı NC, Tokat Y. Incidentally detected PET-avid liver adenomatosis: MRI and 18F-FDG PET-CT findings. Turk J Gastroenterol 2018; 29: 623-4.